Answer:
x= 3
y= 2
Explanation:
The given equations are :
2x-5y = -4 equation 1
x +6y = 15 equation 2
We will multiply the equation:2 by 2
2(x+6y=15)
2x+12y=30 equation 3
Lets call this equation:3
Now we will use the elimination method:
Subtract equation 3 from equation 1:
2x-5y = -4
2x+12y=30
_________
-17y = -34
y= -34/-17
y = 2
Now put the value of y in any equation:
We will use equation 1
2x-5y = -4
2x-5(2)= -4
2x-10= -4
Move the constant to the R.H.S
2x= -4+10
2x=6
Divide both the terms by 2
x= 3
Therefore the solution set is (x,y){(3,2)}....